2000
DOI: 10.1021/jp000902m
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic Investigation of the Self-Assembly Processes of Dialkyl Disulfides and Dialkyl Sulfides on Au(111)

Abstract: The formation of striped phases of dialkyl disulfides and dialkyl sulfides on Au(111) and graphite has been monitored by scanning tunneling microscopy (STM) to investigate differences in adsorption of the sulfide to the gold surface. Striped phases formed by C18H37S- moieties after S−S bond cleavage of dioctadecyl disulfide on the gold surface were observed. On the other hand, self-assembled monolayers (SAMs) of dioctadecyl disulfide and dioctadecyl sulfide adsorbed on a graphite surface displayed long-range, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
90
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 51 publications
7
90
1
Order By: Relevance
“…The cubane-type {Ni 4 } complex in the crystallized state is thermally stable up to 525 K. In literature the formation of highly ordered self-assembled monolayers (SAMs) with thioether-functionalized molecules has been reported [19,20]. Our STM studies do not show, however, a periodic surface morphology related to ordered SAMs, but rather an almost featureless surface.…”
Section: Stability Of Chemisorbed Moleculesmentioning
confidence: 46%
“…The cubane-type {Ni 4 } complex in the crystallized state is thermally stable up to 525 K. In literature the formation of highly ordered self-assembled monolayers (SAMs) with thioether-functionalized molecules has been reported [19,20]. Our STM studies do not show, however, a periodic surface morphology related to ordered SAMs, but rather an almost featureless surface.…”
Section: Stability Of Chemisorbed Moleculesmentioning
confidence: 46%
“…The green line shows the CV of the Au(111) electrode covered with the DOS SAM, which was prepared by immersing the bare Au(111) electrode for 24 h in the DOS solution. The SAM obtained by such a long immersion comprises DOS molecules with the uprightstanding orientation in a higher-density phase [12,13]. No current flows in the entire potential region; hence, the Cu-UPD does not occur on this electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The SAMs of two structures comprising the same molecules are suitable samples to elucidate such a difference clearly. For this purpose, dioctadecylsulfide (DOS) is an ideal choice of molecule, which forms a lamellar structure at low densities and a densely packed triangular lattice at high densities on the Au(111) surface [12,13]. The chain is flat-lying on the former structure, and upright standing on the latter.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advantages, there have only been a limited number of papers involving the formation and structure of thioether SAMs on gold surfaces. [9][10][11][12][13][14][15] It has been revealed that dioctadecyl sulfides (DODS, CH 3 (CH 2 ) 17 S(CH 2 ) 17 CH 3 ) at the initial growth stage form SAMs with striped phases in which the molecular backbones are oriented parallel to the surface, 9 whereas DODS SAMs formed after long immersion have two mixed phases containing closely packed and loosely packed standing-up phases where the molecular backbones are oriented perpendicular to the surface.…”
mentioning
confidence: 99%
“…It has been demonstrated that dialkyl sulfide SAMs on Au(111) were formed through the intact adsorption of molecules without S-C bond cleavage. [9][10][11][12] In general, the adsorption of dialkyl sulfides on gold surfaces often led to the formation of a striped phase in which the two alkyl chains attached to the sulfur are lying flat on the surface such that the observed periodicity of the striped phase is almost identical to an entire molecular length. 11,13,14 Therefore, from the observation of the striped phases with a half molecular length of 1.59 nm for DDS SAMs, we assumed that one of the two alkyl chains attached to the sulfur atom in a bright row switches positions with one of the two alkyl chains bound to the sulfur atom in a neighboring bright row.…”
mentioning
confidence: 99%